2012
DOI: 10.1021/ja305080f
|View full text |Cite
|
Sign up to set email alerts
|

Branched Multifunctional Polyether Polyketals: Variation of Ketal Group Structure Enables Unprecedented Control over Polymer Degradation in Solution and within Cells

Abstract: Multifunctional biocompatible and biodegradable nanomaterials incorporating specific degradable linkages that respond to various stimuli and with defined degradation profiles are critical to the advancement of targeted nanomedicine. Herein we report, for the first time, a new class of multifunctional dendritic polyether polyketals containing different ketal linkages in their backbone that exhibit unprecedented control over degradation in solution and within the cells. High-molecular-weight and highly compact p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 94 publications
(68 reference statements)
1
81
1
Order By: Relevance
“…Although the biodistribution studies demonstrate a tendency toward organ accumulation with increase in molecular weight, we have previously demonstrated the possibility of engineering high MW, hyperbranched polyglycerol based conjugates into biodegradable molecules [47][48][49]. These molecules can be engineered to degrade under specific conditions of pH and temperature, enabling predictable elimination profiles to be achieved.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Although the biodistribution studies demonstrate a tendency toward organ accumulation with increase in molecular weight, we have previously demonstrated the possibility of engineering high MW, hyperbranched polyglycerol based conjugates into biodegradable molecules [47][48][49]. These molecules can be engineered to degrade under specific conditions of pH and temperature, enabling predictable elimination profiles to be achieved.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…fabricated acid degradable poly(ketal amidoamine)‐siRNA nano‐complexes for both in vitro and in vivo delivery studies . Shenoi et al reported the synthesis of polyglycerol‐based hyperbranched polyether polyketals via ring opening polymerization (ROP) and the studies of in vitro degradation, biocompatibility, and in vivo degradation and biodistribution of the same ,. Whiting and Coates developed the synthesis of high molecular weight cyclic polyketal via ROP of bicyclic ketal .…”
Section: Introductionmentioning
confidence: 99%
“…Cell compatibility has been tested using cell viability measurements. Since we have previously reported the biocompatibility of different sized HPGs, only three of the DBHPGs, DBHPG‐3 and DBHPG‐4 (representing low molecular weight) and DBHPG‐5 (representing high molecular weight) were selected for these studies in order to determine whether the incorporation of the disulfide groups modify the biocompatibility of HPGs.…”
Section: Resultsmentioning
confidence: 99%